Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Motor Honda Scoopy pada Konsumen CV. Agung Mandiri Motor - Gregorius Guliling; Walter Obon; Nunsio H. Meylano (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aimed to (1) find out the description of product quality, price and purchasing decisions, (2) find out the influence of product quality and price on purchasing decisions partially and simultaneously. In this research, the population consisted of 100 consumers of CV Agung Mandiri Motor. Due to the limited population, a purposive sampling technique was used for data collection. Questionnaires were used to collect data, which were then analyzed using descriptive methods and inferential statistics, specifically multiple linear regression. The hypothesis was tested using t-tests and f-tests. The descriptive analysis results indicated that the variables of product quality and price have a sufficient impact on purchasing decisions. However, the t-test statistics showed that these variables individually did not significantly affect purchasing decisions. On the other hand, the f-test statistics suggested that all independent variables collectively have a positive and significant effect on purchasing decisions. Additionally, the determination analysis revealed that product quality y and price price contribute to 61 1.6% of purchasing decisions for Honda Scoopy Motorcycles by consumers of CV Agung Mandiri Motor, with the remaining 38.4% influenced by other factors outside the scope of the research variables.